Semiotic Analysis of Kerja Adat Erdemu Bayu in Karonese - Dewi Juni Artha; Syakinah Sinulingga (RIRAI Publisher, 2021)
This research deals with Semiotic Analysis of Kerja Adat Erdemu Bayu in Karonese. This research was aimed to find out the values and meanings contained in the Karo tribe's wedding ceremony so that people do not consider the ceremonial rituals as mere obligations and customs. This research used descriptive qualitative method. The data were taken from the video of the Karonese wedding ceremony on YouTube channel which uploaded on 07 May 2021 and also through interview from an elder who really understands the customs of the Karonese tribe, especially in wedding ceremonies. There were found 15 symbols, they are beka buluh (male’s hood), uis jongkit dilaki (male’s sarong), uis jujung-jujungen (veil), uis ragi barat (sarong), amak tayangen (bed mat), kalang ulu (pillows), perembah (long chloth, baby carrier), beras meciho (pure rice), naruh manuk (egg), sumpit (basket rice), uis nipes (traditional cloth), lampu terlong (oil lamp /lamp), kudin (cooking pot), manuk asuhen (hen), perkakas dapur (kitchen utensils) each of which has an interpretation in the form of advice, prayers and wishes for the bride and groom in living their domestic life.